2020
DOI: 10.1017/s1355617720000193
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of 10-Year Neurocognitive Functioning After Moderate–Severe Traumatic Brain Injury: Early Associations and Clinical Application

Abstract: Objective: This study aimed to explore the 10-year trajectories of neurocognitive domains after moderate–severe traumatic brain injury (TBI), to identify factors related to long-term neurocognitive functioning, and to investigate whether performance remained stable or changed over time. Method: Seventy-nine patients with moderate–severe TBI between the ages of 16 and 55 years were assessed at 3 months, 1, 5, and 10 years postinjury using neuropsychological tests and functional outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…Families are also affected and may have to adapt to a new life with their injured family member being dependent on their assistance and support [10][11][12][13][14]. It has been increasingly recognized that TBI is a chronic condition with multiple and interacting effects on health and wellbeing [15][16][17][18], as a significant proportion of patients continue to experience life-long difficulties and impaired functional status [8,[19][20][21][22]. A challenge in rehabilitation after TBI is the heterogeneous nature of sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…Families are also affected and may have to adapt to a new life with their injured family member being dependent on their assistance and support [10][11][12][13][14]. It has been increasingly recognized that TBI is a chronic condition with multiple and interacting effects on health and wellbeing [15][16][17][18], as a significant proportion of patients continue to experience life-long difficulties and impaired functional status [8,[19][20][21][22]. A challenge in rehabilitation after TBI is the heterogeneous nature of sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…Forslund et al 23 examined 10-year trajectories using the Glasgow Outcome Scale–Extended in moderate to severe TBI survivors and also found a quadratic trajectory in recovery, with a slight decline in functioning toward the 10-yr point, contrary to their stated hypothesis. In contrast, Sigurdardottir et al 24 looked at neurocognitive recovery at 3 mos and at 1, 5, and 10 yrs and found a linear relationship best fit the data. Of note, both of those studies had small sample sizes and were located in Europe, in contrast to the current study focusing on a large cohort of one minority group in the United States.…”
Section: Discussionmentioning
confidence: 94%
“…What happens after acute care discharge, and inability to predict quality of rehabilitation services are missed. In a 10-year longitudinal study by Sigurdardottir et al, 94-96% stabilized in function after the first year [33]. This leaves a narrow window within which to maximize a patient's potential gains.…”
Section: Discussionmentioning
confidence: 98%